(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
ICT Sector reflects strategic importance as an engine of economic growth due to it’s growing revenues and value added in GDP in environments based on knowledge resources. While environments based on the natural resource in Iraq and neighboring Arab countries are suffering the low penetration of ICT which related to the weakness of financial resources allocation within their annual budget. As a result this create environment not supportable to economic and social development.. This research study the economic perspective of the model efficiency of ICT and analysis of its developmental effects. In order to policy and decision-making. Key words: Knowledge economy, Information economy, Millennium Development Goals, ICT Infrastructure, Digital Divide.